The relation between the level of interleukin-23 with duration and severity of ulcerative colitis - Mirsattari, Dariush (Research Institute for Gastroenterology and Liver Diseases, 2012)
AIM: In this study, we determined the relationship between the serum level of IL-23 and the severity of ulcerative colitis (UC) among our population. BACKGROUND: A recent major breakthrough for describing the pathogenesis of intestinal tissue injury in inflammatory bowel disease (IBD) is the pathway related to interleukin-23 (IL-23). PATIENTS AND METHODS: We performed a prospective case-control study on a total of 85 new patients with ulcerative colitis, recruited from a general referral hospital. Forty ethnically matched healthy controls were also enrolled among hospital staffs and analyzed. Serum IL-23 level was quantified using an electrochemiluminescence immunoassay (ECLIA) method with an immunoassay analyzer. RESULTS: The mean serum IL-23 level in the group with ulcerative colitis was significantly higher than the healthy individuals (347.5±130.8 pg/ml versus 233.5±86.3 pg/ml; p< 0.001). There was a positive correlation between the serum level of IL-23 and disease duration (r = 0.27, p = 0.04). Also, a direct relationship was found between the serum level of IL-23 and the severity of disease (mean IL-23 in mild UC = 296.2±51.2 pg/ml; in moderate UC= 356.1±142.9 pg/ml; and in severe UC= 399.3±163.8 pg/ml, p = 0.04). CONCLUSION: Serum level of IL-23 is directly correlated with the duration and severity of ulcerative colitis.